OLIVE OIL TOWARDS TODDLERS’ WEIGHT GAIN - Rita Riyanti Kusumadewi; Sri Handayani; Lely Firrahmawati (P3M Universitas 'Aisyiyah Surakarta, 2022)
Background : Children's growth is influenced by several things, one of them Â is the nutritional intake of the food they consume. When the child has received MPASI, the composition in it must be in accordance with the recommendations from IDAI. That is the proportion for carbohydrates as much as 35-55%, protein which is preferably animal protein as much as 15-20%, fat as much as 35-60%, and fruit or vegetables only as an introduction. Objective: the effect of giving olive oil on the weight gain of toddlers. Methodology: This research is a type of descriptive research. The subjects of the research were toddlers aged 6-24 months in Kemiri KebakkramatKaranganyar. The total population in this study was 109 people with 15 people as samples. This research was conducted in March-June 2021. Results: Most of the respondents gave olive oil regularly every day as much as 86.6%. Most of the people who gave olive oil on a daily basis experienced an 80% weight gain. Conclusion: Giving olive oil as fat in the composition of Â MPASI according to the portion of the dose has an effect on weight gain of toddlers.